Images on childhood in rural South India. - Janssen, Fanny (2005)
ABSTRACT: Among rural South Indian mothers, the preferred birth interval is 36 months and largely related to the health and development of the previous child. To study more in-depth mother's perceptions on the growth, development, and health of their children, explorative fieldwork was conducted in Holikoti, a rural village in South India. The fieldwork encompassed in-depth interviews with 14 mothers and 4 key-informants, and a focus-group discussion among 6 grandmothers. We explored the role of the context, emphasized the development phases, and compared mothers' perceptions with the biomedical viewpoint. Whereas the biomedical development scheme relates the development chances of the child mainly to birth weight, the mothers refer to concepts like muhurta (the astrological time of birth). The mothers relate the growth and development of the child to the appearances of the child, the ability of performing skills, to feeding practices, and much less to the child's behaviour. Among the respondents, a totally different perception of the aetiology of certain illnesses exists, related to traditional beliefs like muttu dosha (evil touch of menstruating women) and dhristi (evil eye). This perceived aetiology also results in specific way of prevention and cure. The long period of breastfeeding. sleeping with the mother and bathing by the mother indicates the existence of prolonged infancy. Care should be taken of the child especially when it is young, i.e. up to three years of age. The ceremonies performed in childhood seem to be related to the protection of the child. Mother's perceptions on the growth, health and development of children, thus, differ substantially from the biomedical development scheme. They reflect much more traditional views, and seem largely determined by the socio-economic and institutional context. This results in both favourable and less favourable childrearing practices. Keywords: child, Growth, Development, Health, Ceremonies, Childrearing, Biomedical development scheme, Qualitative research